Evolution of a cycloaddition-rearrangement approach to the squalestatins: a quarter-century odyssey - Almohseni, HAA; Hodgson, DM (Thieme Publishing, 2020)
The highs, lows, and diversions of a journey leading to two syntheses of 6,7-dideoxysqualestatin H5 is described. Both syntheses relied on highly diastereoselective n -alkylations of a tartrate acetonide enolate and subsequent oxidation-hydrolysis to provide an asymmetric entry to β-hydroxy-α-ketoester motifs. The latter were differentially elaborated to diazoketones which underwent stereo- and regioselective Rh(II)-catalysed cyclic carbonyl ylide formation-cycloaddition and then acid-catalysed transketalisation to generate the 2,8-dioxabicyclo[3.2.1]octane core of the squalestatins/zaragozic acids at the correct tricarboxylate oxidation level. The unsaturated side chain was either protected with a bromide substituent during the transketalisation or introduced afterwards by a stereoretentive Ni-catalyzed Csp 3-Csp 2cross-electrophile coupling. 1 Introduction 2 Racemic Model Studies to the Squalestatin/Zaragozic Acid Core 3 Asymmetric Model Studies to a Keto α-Diazoester 3.1 Dialkyl Squarate Desymmetrisation 3.2 Tartrate Alkylation 3.2.1 Further Studies on Seebach's Alkylation Chemistry4 Failure at the Penultimate Step to DDSQ5 Second-Generation Approach to DDSQ: A Bromide Substituent Strategy5.1 Stereoselective Routes to E -Alkenyl Halides via β-Oxido Phosphonium Ylides5.2 Back to DDSQ Synthesis 6 An Alternative Strategy to DDSQ: By Cross-Electrophile Coupling 7 Alkene Ozonolysis in the Presence of Diazo Functionality: Accessing α-Ketoester Intermediates 8 Summary.